Induced changes in olive oil subjected to various chemical refining steps: A comparative study of quality indices, fatty acids, bioactive minor components, and oxidation stability kinetic parameters - Gharby, Said; Hajib, Ahmed; Ibourki, Mohammed; Sakar, El Hassan; Nounah, Issmail; Moudden, Hamza EL; Elibrahimi, Mohamed; Harhar, Hicham (Chemical Data Collections, 2021)
•The chemical refining process are to obtain a better quality, a more acceptable aspect such as lighter odor and color, and a longer stability of oil.•Chemical composition and Arrhenius kinetic parameters of virgin olive oil and refined olive oil were determined.•The problem of this treatment is that most of refining processes removing also the substances that contribute to the healthy properties and stability of olive oils. We investigated the effects of various chemical refining (CR) steps on the chemical composition and Arrhenius kinetic parameters of virgin olive oil (VOO). Significant differences were highlighted between VOO and refined olive oil (ROO) for almost measured parameters. Moreover, CR induced reductions in measured parameters up to 34% (tocopherols, sterols, and secondary oxidation products), 86% (oxidation primary products), and 96% (free fatty acids, FFAs). Neutralization eliminated FFAs, bleaching increased stigmasta-3,5-diene and the UV extinction coefficient K270, while deodorization increased trans fatty acids. However, CR reduced oil stability and had no significant effects on the fatty acids and iodine value. While reducing FFAs and oxidation products, refining resulted in oils of lower quality (increase of trans fatty acids) and reduced stability, which seemed to be linked to decreases in tocopherols and phytosterols acting as antioxidants. [Display omitted]